DIAGNOSIS LIMA PENYAKIT UTAMA KARENA JAMUR PADA 100 KULTIVAR BIBIT PISANG - Loekas Soesanto; Endang Mugiastuti; Fajarudin Ahmad; . Witjaksono (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2012)
The research which aimed to identify main pathogenic fungi of 100 banana seedling cultivars and their disease intensity was carried out at the Laboratory of Plant Disease, Faculty of Agriculture, Jenderal Soedirman University with samples and field data taking at Indonesian Insitute of Science Bogor. This descriptive research was started by taking samples and field data followed by identification of pathogenic fungi at the laboratory. Variables observed were disease symptoms, colony and pathogenic morphology, kinds of the pathogen, disease intensity, and physical data. Result of the research showed that there were five main pathogenic fungi of the banana seedlings, i.e., Fusarium oxysporum Schlecht. f.sp. cubense, causing Fusarium wilt; Mychosphaerella musicola Mulder, causing Mycosphaerella leaf spot or Sigatoka; Cordana musae (Zimm.) Hohn., causing Cordana leaf spot; Curvularia lunata, causing leaf spot; and Cladosporium musae Mason, causing speckle. From 100 banana seedling cultivars observed, Fusarium oxysporum f.sp. cubense was the most frequently found with the intensity of 1.4-72%, followed by Curvularia lunata, Mychosphaerella musicola, Cladosporium Musae, and Cordana musae with the intensity of 1-32, 2-18, 2-24, and 3-23%, respectively.